THE USE OF WHATSAPP APP IN DISTANCE LANGUAGE LEARNING IN PANDEMIC COVID-19: A CASE STUDY IN NAHDLATUL ULAMA UNIVERSITY OF YOGYAKARTA - Adhan Kholis (LET: Linguistics, Literature and English Teaching Journal, 2020)
Lately, pandemic covid-19 has changed the educational field including learning methods from conventional learning to distance learning. This shift needed more adaptation for all parts like stakeholders, teachers, and also students. Evidently, various efforts have been made by teachers in simplifying teaching and learning such as applying some digital technologies like WhatsApp App, an asynchronous communication to reach the students’ presence with any spaces and time. This study aimed to describe and to evaluate the use of utilizing WhatsApp App in distance language learning for the English Education Department Students of Nahdlatul Ulama University of Yogyakarta. The research design of this study was a case study. Furthermore, this study gave the detailed information, description, and understanding deeply in relation to the use of WhatsApp App in remote teaching. Students’ perception and the factors affecting the effectiveness were investigated through a questionnaire. The results showed that WhatsApp App can support and helped the language learning to be more effective and efficient for the reason that it was accessible and low technology for distance learning. The students were more responsive and enthusiastic in joining the class. Indeed, it has given more facilities and satisfaction in practice.